IMPLEMENTATION OF THE 'æ•°å—ç´ å…» (SHÃ™ZÃŒ SÃ™YÇNG)' INSTRUMENT TO MEASURE THE DIGITAL LITERACY LEVEL OF MANDARIN LANGUAGE EDUCATION STUDENTS - Ventivani, Aiga; Muyassaroh, Lukluk Ul; Laksana Sakti, Karina Fefi; Masrur, Muhammad Farhan (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The current presence of the internet undeniably facilitates and accelerates individuals' ability to access and disseminate information, even leading to an information explosion. To manage this situation, digital competence is required to face the 6.0 era. The world's shift toward complete digitalization pushes humans to quickly adapt to digital infrastructure and digital services. To address this, humans need skills referred to as digital literacy. This research emphasizes the measurement of primary data, specifically objective digital literacy levels, using numerical data and statistical analysis. The study aims to determine the digital literacy level of Mandarin language students using the "æ•°å—ç´ å…»" (Digital Literacy) instrument. The results of this study indicate that the digital literacy level of Mandarin students is at a fairly good level, with an overall average score of 3.25. The Digital Literacy Index across all dimensions falls into the advanced category (81.25%). Among the eight dimensions, two are categorized as "good," namely the Collaboration Dimension (3.45) and Social-Cultural Understanding (3.41). The other six dimensions fall into the "fairly good" category, with scores ranging from 3.11 to 3.40, including Functional Skills (3.40), Creativity (3.22), Communication (3.19), Information Searching and Selection Ability (3.11), Critical Thinking (3.15), and Digital Safety (3.14).